Overview of Family Functions in Bola Hamlet, Bola Village - Gabriel Mane; Maria Kornelia Ringgi Kuwa; Marianus Oktavianus Wega; Antonia Rensiana Reong; Agutina Ita (Indonesian Journal of Global Health Research, 2024)
The family serves as the foundational unit of society, playing a critical role in maintaining the physical, mental, and social well-being of its members. This includes responsibilities for caregiving, particularly for children, parents, and members requiring special attention. Families are tasked with meeting physical, emotional, and social needs while ensuring access to appropriate health services. Additionally, they provide a safe and nurturing environment, fostering the holistic development of children. Families act as the first line of defense against harm, violence, and abuse and are especially vital in protecting vulnerable groups such as children, pregnant women, and the elderly. According to data from the Sikka Regency Health Office, there are 106,627 families in the region, including 118 families in Bola Hamlet. Objective to examine the functions of families in Bola Hamlet. This quantitative research employs a descriptive design aimed at understanding and outlining current conditions within a community. The study involved a population of 168 families and utilized an incidental sampling technique for data collection, with questionnaires as the primary instrument. Data yang di kumpulkan di klarifikasi dan di tabulasi, kemudian di olah serta disajikan dalam bentuk table frekuensi atau variabel penelitian di interpretasikan dengan menggunakan skala ordinal yaitu. Baik > 75 – 100%, cukup 50 – 74 %, kurang < 49 % The findings reveal that the most prominent family function is the socialization function, with 60 respondents (50%) categorized as sufficient. This is followed by the affective function, with 50 respondents (42%) in the sufficient category; the religious function, with 48 respondents (41%); the economic function, with 58 respondents (49%); and, lastly, the family care function, which showed the lowest performance, with only 33 respondents (27%) categorized as sufficient. This study provides an overview of family functions, including affective, socialization, economic, religious, and family care functions, concerning demographic factors such as age, gender, education, and occupation.